Effect of Astaxanthin Supplementation in Preventing Anemia in Head and Neck Cancer Patients Receiving Cisplatin Chemotherapy - Aminullah, Yusuf; Subagio, Hertanto Wahyu; Santosa, Damai; Naftali, Zulfikar (Indonesian Society for Cancer Chemoprevention, 2023)
The incidence of anemia due to reactive oxygen species (ROS) in patients with head and neck cancer (HNC) can be caused by a side effect of cisplatin chemotherapy, namely myelosuppression. In the presence of ROS, external antioxidants are needed, including astaxanthin as an antioxidant to neutralize and fight ROS in preventing anemia. This study aims to prove and analyze the antioxidant effect of astaxanthin in preventing anemia in HNC patients due to cisplatin chemotherapy for 3 weeks. The study design was a randomized controlled trial pre-post test design, involving 42 research subjects who were randomly divided into two groups, then 3 cc of blood was taken I to check the hemoglobin level and the number of erythrocytes. The treatment group was given astaxanthin 2x4 mg and the control group was given a combination of vitamin C 1x500 mg and vitamin E 1x250 IU for 3 weeks then 3 cc of blood was taken II to check hemoglobin levels and erythrocyte counts. The independent variable is intake of astaxanthin, the dependent variable is hemoglobin level and the number of erythrocytes and the confounding variables are age, sex, type of HNC, stage of HNC, ECOG and BMI. Data analysis was performed by the Descriptive test, Levene test, Shapiro Wilks, Wilcoxon test, and Mann-Whitney test. The significance of the hypothesis test was obtained with p<0.05. The 42 research subjects met the inclusion criteria, most aged between 41-50 years, male and female ratio 2:1, The most HNC were Nasopharyngeal Cancer, the most HNC stage was stage IV, the most HNC performance status was ECOG I and the most HNC patients had normal BMI. There was a significant difference in hemoglobin levels p=0.012 (p<0.05) and the number of erythrocytes, p=0.04 (p<0.05) between the treatment and control groups. There was a significant difference in hemoglobin levels after therapy in the treatment and control groups p=0.012 (p<0.05) and the number of erythrocytes p=0.04 (p<0.05) between the treatment and control groups. Astaxanthin can prevent anemia in the form of decreased hemoglobin levels and the number of erythrocytes in HNC patients who receive cisplatin chemotherapy.Keywords: astaxanthin, anemia, HNC, cisplatin, ROS.